Kajian Literatur Tersistematis (SLR) Pengaruh Penghijauan untuk Peningkatan Kesehatan Mental dan Performa Siswa di Lingkungan Sekolah - Rahardjo, Astrid Hapsari; Bachtiar, Firmansyah; Doloksaribu, Hendrik Poltak (Local Engineering, 2025)
The concept of biophilia is widely recognized as a way to reconnect humans with the natural environment, based on the understanding that humans are inherently part of nature. Studies have shown that this reconnection can have positive effects, including improved mood. Among school children, this benefit is often reflected in better academic performance. In architecture, the integration of natural elements is commonly linked to biophilic concepts and design patterns. This literature review examines studies conducted across various fields between 2014 and 2024. The final analysis presents methods and key findings of these studies, identifies existing research gaps, and highlights potential directions for future research in architecture.